Understanding the global dynamics of the equatorial ionosphere in Africa for space weather capabilities: A science case for AfrequaMARN. (1st October 2019) - Lawal, Hammed A.; Lester, Mark; Cowley, Stanley W.H.; Milan, S.E.; Yeoman, T.K.; Provan, Gabby; Imber, Suzie; Rabiu, A.Babatunde
Abstract: The equatorial region of the Earth's ionosphere is one of the most complex ionospheric regions due to its interactions, instabilities, and several unresolved questions regarding its dynamics, electrodynamics, and physical processes. The equatorial ionosphere overall spans three continents with the longest region being that over the African continent. Satellite observations have demonstrated that very large differences exist in the formation of ionospheric irregularities over the African sector compared with other longitudinal sectors. This may be a consequence of the symmetric shape of the magnetic equator over the continent and the lack of variability in latitude. In this paper, we propose a science campaign to equip the African sector of the magnetic equator with ground-based instruments, specifically magnetometers and radars. The network of radars proposed is similar in style and technique to the high-latitude SuperDARN radar network, while the magnetometers will form an array along the equatorial belt. These two proposed space physics instruments will be used to study this region of the equatorial ionosphere over a long interval of time, at least one solar cycle. The deployment of an array of magnetometers (AfrequaMA) and a radar network (AfrequaRN) in the African sector of the magnetic equator is jointly called the Africa Equatorial Magnetometer Array and Radar Network (AfrequaMARN), which will provide simultaneous observations of both electric and magnetic variations over the African sector. We also examine the possible science questions such a magnetometer array and radar network would be able to address, both individually and in conjunction with other space-based and ground-based instrumentation. The proposed projects will clearly improve our understanding of the dynamics of the equatorial ionosphere and our understanding of its role in balancing the large-scale ionospheric current system, and will contribute to our ability to adequately model ionospheric and plasmaspheric densities. It will also enhance our understanding of global ionospheric processes, which will improve the space weather capabilities of the African and international space science communities.